PERENCANAAN SALURAN IRIGASI PRIMER DAN SEKUNDER PADA D.I BARINGIN RAMPANAI KECAMATAN BATIPUH KABUPATEN TANAH DATAR - Reski, Rahmad; Masril, Masril; Susanti Yusman, Ana (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2024)
The Baringin Rampanai irrigation area currently only has the capacity to irrigate a rice field area of ±80 Ha out of a total of ±120 Ha of rice field area. The aim of constructing irrigation canals is to develop and determine the dimensions of effective irrigation canals and increase agricultural production by providing supporting facilities so that water can be distributed evenly. At the research method stage of processing rainfall data the author used the gumbel, haspers and rational methods. With calculation results for R3 in 457 mm and R5 in 1174 mm. Based on the calculation of the planning dimensions of the primary channel with bottom width b = 175 cm, height h = 170 cm and top width B = 300 cm, and secondary channel 1 with bottom width b = 135 cm, height h = 120 cm and top width B = 210 cm, secondary 2 with bottom width b = 95 cm, height h = 120 cm and top width B = 200 and secondary 3 with bottom width b = 120 cm, height h = 90 cm and top width B = 200 cm. Primary channel planning calculation where the planned Q value of 59.76 m3/s is greater than Q max 58.03 m3/s, secondary channel 1 where the planned Q value is 20.40 m3/s greater than Q max 19.47 m3/s , secondary channel 2 Q plans 11.69 m3/s greater than Q max 10.37 m3/s, and secondary channel 3 Q plans 10.45 m3/s greater than Q max 9.87 m3/s. So the planned channel dimensions can accommodate maximum rainfall discharge.Keywords : Irrigation Channels, Primary, Secondary, Gumbel, Haspers, Rational